2002
DOI: 10.1097/00003226-200203000-00007
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine in Chronic Blepharitis

Abstract: NAC is thought to increase FBUT and improve mucous fern pattern by blocking lipid peroxidation in chronic blepharitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Two studies compared a topical immunosuppressant agent with placebo (Perry 2006) or with topical antibiotics plus steroids (Rubin 2006). One study evaluated a treatment regimen of topical antibiotics and steroids plus warm compresses and artificial tears with or without supplementation with an oral mucolytic agent (Yalçin 2002). A topical mucolytic agent was compared with artificial tears in another study (Akyol-Salman 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies compared a topical immunosuppressant agent with placebo (Perry 2006) or with topical antibiotics plus steroids (Rubin 2006). One study evaluated a treatment regimen of topical antibiotics and steroids plus warm compresses and artificial tears with or without supplementation with an oral mucolytic agent (Yalçin 2002). A topical mucolytic agent was compared with artificial tears in another study (Akyol-Salman 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Em se tratando da produção lacrimal, o grupo com formulação oftálmica (grupo AAP) apresentou melhor efeito com relação ao aumento da produção lacrimal, que está relacionada pela associação dos vários componentes integrantes dessa formulação, como o álcool polivinílico a 1,4%, agente umectante que estabiliza a película lacrimal e impede sua ruptura, incrementando a viscosidade , a acetilcisteína, que possui propriedade mucolítica, anticolagenolítica e antioxidante (Yalçin et al, 2002;Aldavood et al, 2003;Hongyok et al, 2009), e a pilocarpina, droga parassimpatomimética, que possui efeito lacrimoestimulante, porém pode induzir irritação ocular, caracterizada por hiperemia conjuntival e blefaroespasmo, que não foi observado no presente experimento, talvez devido à sua diluição na formulação oftálmica (Andrade, 2008). Em um estudo em cães, foi relatado que a pilocarpina colírio em várias concentrações (0,25; 1,0 ou 2,0%) não alterou significativamente a produção lacrimal, porém a frequência de instilação realizada neste estudo foi nos dias quatro, seis e oito, o que pode ser considerada baixa e ser responsável pelos resultados obtidos (Smith et al, 1994).…”
Section: Discussão E Conclusãounclassified
“…32 With systemic administration of NAC, Yalçin et al have shown improved mucous fern quality and FBUT in patients with chronic blepharitis. 33 Since MGD and dry eye often coexist, 1-6 topical administration of NAC may have been effective in our patients, in part, by alleviating dry eyes.…”
Section: Discussionmentioning
confidence: 91%